Quantitative liver SPECT/CT is a novel tool to assess liver function, prognosis, and response to treatment in cirrhosis - Kaur, Amritjyot; Verma, Nipun; Singh, Baljinder; Kumar, Ajay; Kumari, Sunita; De, Arka; Sharma, Ratti Ram; Singh, Virendra (Frontiers in Medicine, 2023)
Background Functional liver reserve is an important determinant of survival in cirrhosis. The traditional indocyanine green test (ICG) is cumbersome. Hence, we developed and validated a novel liver imaging, a hybrid of SPECT and CT (Q-SPECT/CT), for evaluating disease severity, outcomes, and response to treatment in decompensated cirrhosis (DC). Methods We recruited a cohort of DC patients at a tertiary institute between 2016–2019. First, we standardized the Q-SPECT/CT across a predefined range of volumes through phantom experiments. Then we performed clinical and laboratory evaluations, ICG test (retention at 15 min), and Q-SPECT/CT at baseline and 12 months of granulocyte colony-stimulating factor (G-CSF) and standard medical treatment (SMT). Results In 109 DC patients, 87.1% males, aged 51 ± 10 years, MELD: 14 (7–21), the percent quantitative liver uptake (%QLU) on Q-SPECT/CT exhibited a strong correlation with CTP (r = −0.728, p < 0.001), MELD (r = −0.743; p < 0.001) and ICG-R-15 (r = −0.720, p < 0.001) at baseline. %QLU had the maximum discrimination (AUC: 0.890–0.920), sensitivity (88.9–90.3%), specificity (81.2–90.7%), and accuracy (85.8–89.4%) than liver volumes on Q-SPECT/CT or ICG test for classifying patients in CTP/MELD based prognostic categories. A significant increase in %QLU (26.09 ± 10.06 to 31.2 ± 12.19, p = 0.001) and improvement in CTP/MELD correlated with better survival of G-CSF treated DC patients (p < 0.05). SMT did not show any improvement in Q-SPECT/CT or clinical severity scores (p > 0.05). %QLU > 25 (adj.H.R.: 0.234, p = 0.003) and G-CSF treatment (adj.H.R.: 0.414, p = 0.009) were independent predictors of better 12-months survival in DC. Conclusion Q-SPECT/CT (%QLU) is a novel non-invasive, diagnostic, prognostic, and theragnostic marker of liver reserve and its functions in cirrhosis patients. Clinical trial registration Clinicaltrials.gov, NCT02451033 and NCT03415698.